EXPLORING LIPID LOWERING ACTIVITY OF CASSIA FISTULA AND SIMVASTATIN, IN HYPERLIPIDEMIC MICE - Usman Nawaz; Nasim Ilyas; Hussain Ali (Journal of University Medical & Dental College, 2019)
OBJECTIVE: To compare lipid lowering activity of aqueous extract of Cassia ﬁstula and Simvastatin in National Institute of Health Sciences, Islamabad.STUDY DESIGN: A Randomized controlled experimental study.PLACE AND DURATION OF STUDY: The study was conducted from 1st Feb – 31st Apr 2016 (8 week duration) in National Institute of Health Sciences, Islamabad.METHODOLOGY: Fifty male Balb/c mice randomly divided into 5 groups, Group A (control), Group B received (2% cholesterol diet), Group C (2% cholesterol diet + simvastatin 1mg/kg), and Group D and E (2% cholesterol diet + aqueous extract of Cassia ﬁstula leaves 250 and 500 mg/kg) respectively. On completion of 8 week duration blood samples were collected and assessed for TC, TGs, LDL and HDL.RESULTS: After 8 weeks, Group B, showed increased cholesterol (170.90), triglycerides (124.20) and LDL-C (102.40), and decline in HDL-C (23.00). Cassia ﬁstula, simvastatin signiﬁcantly decreases the levels of these parameters in mice. High doses of Cassia ﬁstula reduces lipid levels (95.60) more eﬀectively than the simvastatin. Also, Cassia ﬁstula increased HDL-C level (44.80) in mice as compared to simvastatin.CONCLUSION: At high dose, aqueous extract of Cassia ﬁstula leaves decreases lipid levels more eﬀectively than simvastatin in diet induced hyperlipidemic mice.